History of Bangladesh, 1704-1971 : vol. 1 - Islam, Sirajul; Hussain, Aklam; Asiatic Society of Bangladesh (Dhaka, Bangladesh : Asiatic Society of Bangladesh, 2007)
Contributed articles.
Includes bibliographical references and index.
Keywords: Bangladesh -- History; Bengal (India) -- History